Management of Personnel Administration Services at the Bolaang Mongondow Education Service Branch Office - Mokoginta, Sadli Rais; Masengi, Evi; Dilapanga, Abdul Rahman (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This study aims to explore, analyze and interpret the description of the Management of Personnel Administration Services at the Bolaang Mongondow Education Office Branch Office. The research method used is descriptive qualitative research method and looking for the necessary data by direct observation at the Bolaang Mongondow Education Office. Research informants are people or parties related to research who can provide information about various real conditions. The results of the research conducted were obtained The management of personnel administration services at the Bolaang Mongondow education office branch office has been running according to the established standard operating procedures. The services provided are quite good and satisfying because based on the experience of service users that the administration of the proposal is not complicated and is completed on time. In addition to distance constraints that do not really affect the service.